2015
DOI: 10.1111/ijs.12466
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment and Prevention of Cerebral Small Vessel Disease: A Review of Potential Interventions

Abstract: Small vessel disease encompasses lacunar stroke, white matter hyperintensities, lacunes and microbleeds. It causes a quarter of all ischemic strokes, is the commonest cause of vascular dementia, and the cause is incompletely understood. Vascular prophylaxis, as appropriate for large artery disease and cardioembolism, includes antithrombotics, and blood pressure and lipid lowering; however, these strategies may not be effective for small vessel disease, or are already used routinely so precluding further detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
174
0
24

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(200 citation statements)
references
References 69 publications
2
174
0
24
Order By: Relevance
“…43 Of these, observational studies have shown a reduced risk of dementia associated with long-term use of nonsteroidal anti-inflammatory drugs, statins, H2-receptor antagonists, and calcium channel blockers, which may, in part, be attributable to anti-inflammatory or antiangiogenic effects. Although none have proven effective in treatment of AD, [44][45][46] the effect of longterm use on prevention of dementia has not been assessed in trials.…”
Section: Discussionmentioning
confidence: 99%
“…43 Of these, observational studies have shown a reduced risk of dementia associated with long-term use of nonsteroidal anti-inflammatory drugs, statins, H2-receptor antagonists, and calcium channel blockers, which may, in part, be attributable to anti-inflammatory or antiangiogenic effects. Although none have proven effective in treatment of AD, [44][45][46] the effect of longterm use on prevention of dementia has not been assessed in trials.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction Small vessel diseases of the brain are an important cause of stroke and dementia (Pantoni, 2010;Bath and Wardlaw, 2015). Our ability to accurately identify these diseases using neuroimaging markers has improved considerably in recent years (Wardlaw et al, 2013c), with increasing interest in the role of small vessel pathology in traditionally "non-vascular" dementias, such as Alzheimer's disease (AD).…”
Section: Svci Subcortical Vascular Cognitive Impairment (Svmci and Svad)mentioning
confidence: 99%
“…Whether the treatment of CVRFs can prevent WMH progression and LI occurrence in community-dwelling older people is not well known. 4,6 Some study results suggest that antihypertensive treatment might reduce WMH progression.7-9 Cholesterol-lowering drugs might also hinder WMH increase, although results are inconclusive. 4,6,[10][11][12] Clinical guidelines recommend secondary prevention after symptomatic LI, involving BP lowering, smoking cessation, antiplatelet…”
mentioning
confidence: 99%
“…Whether the treatment of CVRFs can prevent WMH progression and LI occurrence in community-dwelling older people is not well known. 4,6 Some study results suggest that antihypertensive treatment might reduce WMH progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation